The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.3329/bvet.v30i1.16283
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high voltage electrical stimulation on the rate of pH decline, meat quality and colour stability in chilled beef carcasses

Abstract: Fifty beef carcasses were used to determine the effects of High Voltage Electrical Stimulation (HVES, 800 Volts) on pH and meat quality. Meat from M. longissimus dorsi was examined for pH and temperature at 1, 2, 5, 10 and 24 hours, while tenderness and colour were examined seven days after slaughter. HVES decreased the pH of the meat and accelerated rigor mortis (P<0.05). HVES improved tenderness and colour compared with the control group across the ageing period at 4oC. It is suggested that HVES had posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 29 publications
2
1
0
Order By: Relevance
“…The stimulated carcasses had lower pH values at 1, 3, 6, 9, 12, and 24 hours post mortem compared with the NES carcasses ( Figure 1). Mombeni et al (2013) reported results that were similar to what was observed in the present study in terms of the effect of ES on the decline in beef carcass pH up to 24 hours post mortem. In other species, Cetin et al (2012) found that the stimulated carcasses of lamb and goat with different levels of voltage (50, 100, and 250 V) resulted in a significant pH decrease up to 24 hours post mortem compared with non-stimulated ones.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The stimulated carcasses had lower pH values at 1, 3, 6, 9, 12, and 24 hours post mortem compared with the NES carcasses ( Figure 1). Mombeni et al (2013) reported results that were similar to what was observed in the present study in terms of the effect of ES on the decline in beef carcass pH up to 24 hours post mortem. In other species, Cetin et al (2012) found that the stimulated carcasses of lamb and goat with different levels of voltage (50, 100, and 250 V) resulted in a significant pH decrease up to 24 hours post mortem compared with non-stimulated ones.…”
Section: Resultssupporting
confidence: 92%
“…As reviewed by Bekhit et al (2014) and Huang et al (2016), ES accelerates carcass pH decline, causing early activation of protease enzymes and protein degradation, which increases the meat tenderization process. The observed effect of ES on SF agrees with previous works (Li et al, 2006;McKenna et al, 2003;Nazli et al, 2010;Mombeni et al, 2013;Agbeniga & Webb, 2014). As anticipated, the SF values were affected significantly by age at slaughter (Table 3).…”
Section: Figure 4 Colorimetric Traits Of Baggara Beef Muscle Samples supporting
confidence: 92%
See 1 more Smart Citation